NGHIÊN CỨU MỘT SỐ ĐẶC ĐIỂM SINH HỌC CỦA LOÀI TRÙNG CHÂN GIẢ CÓ VỎ Arcella gibbosa TRONG CÁC MÔI TRƯỜNG NUÔI CẤY QUY MÔ PHÒNG THÍ NGHIỆM - Nguyễn, Thị Chinh; Trần, Quốc Hoàn; Đỗ, Tất Thịnh; Trần, Thị Nhàn; Nguyễn, Thị Kim Oanh (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
STUDY ON SOME BIOLOGICAL CHARACTERISTICS OF THE TESTATE AMOEBA (Arcella gibbosa) IN LABORATORY SCALE CULTURE MEDIUMThe study aimed to determine how different culture mediums affected the growth and morphology of the testate amoeba Arcella gibbosa Penard, 1890 in the laboratory. This study experimented with two main ways of culturing (MWC and distilled water with rice). The results revealed that Arcella gibbosa had shell diameter (42.12 - 59.10 µm), shell height (27.14 - 37.14 µm), and mouth diameter (8.12 - 21.01 µm). Comparing the species density of Arcella gibbosa over time in intermittent growth circumstances showed that the species density in distilled water with rice was much greater than in MWC medium. Distilled water medium supplemented with rice was shown to be more suited than MWC medium for growing Arcella gibbosa. The findings of this study would serve as the basis for further investigations into the construction of a collection of strains, strains of organisms that are difficult to culture in the laboratory, as well as research studies on environmental toxicity and biomarkers...